2018
DOI: 10.1021/acs.langmuir.8b01187
|View full text |Cite
|
Sign up to set email alerts
|

Stability Mechanism of Nitrogen Foam in Porous Media with Silica Nanoparticles Modified by Cationic Surfactants

Abstract: This work aims at studying the effect of electrostatic interactions between cationic surfactants and silica nanoparticles (NPs) on foam stability in porous media. The physio-chemical property of NPs, the gas-liquid interface properties, the foam flow characteristics, together with the stability under different concentrations of surfactant and NPs were investigated and compared. It was found that the affinity of silica NPs to the surface is tunable by variation of surfactant concentrations. NPs and surfactants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(10 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…When CTAB molecules and SNPs were added to aqueous phase simultaneously, the adsorption of CTAB molecules on SNP surface 19 endowed the SNPs with surface activity. Hence, these decorated SNPs are able to anchor and assemble at bubble surface (Figure 2a).…”
Section: Industrial and Engineering Chemistry Researchmentioning
confidence: 99%
“…When CTAB molecules and SNPs were added to aqueous phase simultaneously, the adsorption of CTAB molecules on SNP surface 19 endowed the SNPs with surface activity. Hence, these decorated SNPs are able to anchor and assemble at bubble surface (Figure 2a).…”
Section: Industrial and Engineering Chemistry Researchmentioning
confidence: 99%
“…synthesized a new type of foam fracturing uid with acrylamide and cetyltrimethylallyl ammonium chloride, which improved the stability of the foam due to the association structure. Wu [12] et al studied the effect of electrostatic interaction between cationic surfactants and silica nanoparticles (NPs) on foam stability in porous media, and found that NPs and surfactants greatly improved foam stability.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the advantages of foams, a major issue for this technology is the foam stability in deep reservoirs (with high temperature and pressure) especially when crude oil is present since quite a few reports have observed the detrimental effect of hydrocarbons on foam stability. Furthermore, surfactants are prone to detach from the bubble surface when foams are subjected to high-temperature and salinity. As reported, the foam stability is heavily dependent on bulk and surface viscosities, micelle concentration, disjoining pressure, hydrophobic interactions, surface tension (equilibrium and dynamic), and surfactant adsorption at the air/water interface. On the basis of these mechanisms, substantial efforts have been made in the past decades aiming to boost foam stability and extend foam longevity in reservoirs.…”
Section: Introductionmentioning
confidence: 99%
“…), as illustrated in Figure . Through adsorption and aggregation in foam films, NPs can increase film thickness and dilational viscoelasticity, which consequently decelerates liquid drainage and film thinning. ,, In addition, the capability of the interface to bear in-plane shear has been recently demonstrated as a key factor in stabilizing droplets . As for polymers, the predominant stabilizing mechanism is to significantly increase the bulk fluid viscosity of the foaming solution.…”
Section: Introductionmentioning
confidence: 99%